Statistics for management and economics - Mendenhall, William. (Duxbury Press, 1993)
What is statistics? Describing sets of measurements. Probability. Random variables and probability distributions. Three useful discrete probability distributions. The normal and other continuous probability distributions. Sampling and sampling distributions. Large-sample estimation. Large-sample tests of hypotheses. Inferences from small samples. The analysis of variance. Linear regression and correlation. Multiple linear regression. Elements of time series analysis. Forecasting based on time series models. Quality control techniques. Survey sampling. Analysis of enumerative data. Nonparametric statistical methods. The decision analysis process.